Coal reservoir as a natural bioreactor for methane formation from coal and carbon dioxide - Yixuan Zhou; Linan Su; Xianbo Su; Weizhong Zhao (Bioresource Technology, 2026)

Genomic insights into adaptation and microevolution of two novel non-AOA Nitrososphaeria, Acidarchaeum fankouense and Thermosulfuris yongpingense, in acid mine drainage ecosystems - Licao Chang; Xikai Su; Wenzhe Hu; Yun Fang; Jun Liu; Jintian Li; Linan Huang; Wensheng Shu (Systematic and Applied Microbiology, 2026)

Synergistic utilization of desulfurization gypsum and flue gas for the sustainable synthesis of nano-CaCO3 - Lufei Wang; Linan Su; Mingxu Li; Can Lv; Weizhong Zhao (Chemical Engineering Journal, 2026)

Formation mechanisms of H2S in coal seam of southern Junggar Basin in Xijiang, China - Linan Su; Yixuan Zhou; Weizhong Zhao; Wenjie Zhao (Fuel, 2026)

CO2 sorption induced mechanical response of Beetaloo shale - Umar Farooq; Klaus Regenauer-Lieb; Abolfazl Hashemi; Linan Su; Hamid Roshan (International Journal of Coal Geology, 2025)

Viral insights into the acidification of sulfidic mine tailings - Xikai Su; Jun Liu; Licao Chang; Wenzhe Hu; Yun Fang; Jintian Li; Linan Huang; Wensheng Shu; Hailiang Dong (Journal of Hazardous Materials, 2025)

Integrated response surface and machine learning approach: Experimental optimization and DFT analysis for NaN3 removal via NaClO oxidation - Yunfeng Tan; Jiangzhou Qin; Shengquan Chang; Shengqiang Ma; Linan Su; Nengsheng Liu; Quanlin Zhao; Xintao Wang; Chenxi Li; Jinmao Ma; Kun Wu; Zhengfang Ye (Journal of Water Process Engineering, 2025)

Mechanisms of strain rate-dependent response of naturally fractured coal - Linan Su; Hamid Roshan (International Journal of Coal Geology, 2025)

Graphite-enhanced methanogenesis in coal measure shale anaerobic digestion: Implications for increasing gas yield and CO2 utilization - Qian Wang; Fubo Gao; Xianbo Su; Yi Jin; Weizhong Zhao; Hongyu Guo; Linan Su; Liangwei Xu; Xiaowei Shi; Laizhong Ding; Shiyao Yu (Chemical Engineering Journal, 2025)

A Theoretical and Experimental Study on Asperity Damage-Driven Strain Rate Dependency of Fractured Coal - Linan Su; Hamid Roshan (Rock Mechanics and Rock Engineering, 2024)
Asperities within pre-existing fractures of coals can experience local damage during the fracture closure due to external loading. Previous research postulates that this local asperity damage can lead to strain rate-dependency without causing permanent deformation to the bulk of the coal specimens. This study aims to comprehensively investigate this behavior by developing a theoretical model that characterizes the strain rate-dependency driven by fracture asperity damage in coal. To achieve this objective, an initial series of micro-scale mechanical tests are conducted on joint specimens to establish a model for effective stress acting on asperities. Building upon this model, a theoretical foundation is further developed to describe the strain rate-dependent asperity damage evolution and resulting energy dissipation. These frameworks are subsequently incorporated into elasticity and damage mechanics to capture the strain rate-dependent stress–strain relationships. To validate the proposed model across multiple scales, additional triaxial tests on core-scale specimen and micro-scale mechanical tests on joint specimens are performed. The experimentally measured strain rate-dependency aligns well with the predictions of the proposed model, indicating a successful development of a robust model. The results of the model developed in this study reveal that the strain rate-dependency in fractured coals is governed by several factors, including asperity damage, mechanical properties of the coal specimens and effective stress acting on asperities of pre-existing fractures within the bulk of coal. Moreover, it is shown that the effective stress acting on asperities is significantly affected by both applied normal stress and joint roughness coefficient (JRC). The insights derived from this study demonstrate that the strain rate-dependency induced by micro-scale asperity damage of pre-existing fractures leads to observable strain rate-dependency in bulk specimens at core-scale and the proposed model can adequately capture this behavior.

Heparin mimicking sulfonated polyester synergistically promotes bacterial Infected-Wound healing with ROS responsive cinnamaldehyde based prodrugs - Haiwei Liu; Pengfei Shan; Yingwen Lu; Xiaoyue Lian; Feng He; Jinxiang Xiao; Linan Qiu; Zhenghao Liu; Zuobin Gan; Qingshan Yan; Yupeng Qiu; Wenwen Lin; et al. (Chemical Engineering Journal, 2024)

Natural gas desorption versus laboratory gas adsorption with pore shrinkage - Linan Su; Hamid Roshan (Fuel, 2024)

Effect of Pore Pressure on Strain Rate-Dependency of Coal - Linan Su; Mohammed Abdul Qadeer Siddiqui; Hamid Roshan (Rock Mechanics and Rock Engineering, 2023)
Viscoelastic strain rate-dependent behaviour of coal is critical in several subsurface engineering applications especially coal seams gas production. Such rate dependency is controlled by the interaction between coal bulk and gas sorption (a sorbing gas) or gas pressure (a non-sorbing gas). Despite the research conducted to date, the gas pressure effect (non-sorbing) on the viscous behaviour of sediments in particular coal remains unexplored. We, therefore, investigate the strain rate-dependent mechanical behaviour of coal under isotropic loading to specifically explore the effect of gas pressure (Helium) on its rate dependency eliminating the sorption effect. We perform a set of triaxial experiments on coal specimens at dry and pressurised gas (Helium) conditions under different strain rates under isotropic loading. The experimental results show that all coal specimens have viscoelastic strain rate dependency at a dry condition where viscous effect increases with strain rate. As a result, the bulk modulus of the specimens increases with the increase in strain rates. This strain rate dependency response, however, reduces with an increase in pore pressure and vanishes at a certain pore pressure under the same effective stress to that of dry specimens. We further employ X-ray micro-Computed Tomography (XRCT) to 3D scan a coal specimen saturated with Krypton gas undergoing different loading rates to shed light on the micro-mechanisms of gas pressure effect on specimens’ rate dependency. The XRCT results show that gas can be trapped in small-scale fractures and pores during the loading process leading to a localised undrained response that can stiffen the specimen and reduce its ability to show viscous rate dependency. The obtained results are significant in optimizing coal seam gas production and coal seam gas drainage applications.

Theory and Application of Pseudo-Reservoir Hydraulic Stimulation for Coalbed Methane Indirect Extraction in Horizontal Well: Part 1—Theory - Qian Wang; Xianbo Su; Linan Su; Hongyu Guo; Jinxing Song; Zengliang Zhu (Natural Resources Research, 2020)

Theory and Application of Pseudo-Reservoir Hydraulic Stimulation for Coalbed Methane Indirect Extraction in Horizontal Well: Part 2—Application - Qian Wang; Xianbo Su; Linan Su; Hongyu Guo; Jinxing Song; Zengliang Zhu (Natural Resources Research, 2020)